Degradation and stabilization of thermoplastic ether-ester elastomers (TPE-E) - Szymczyk, A.; Rosłaniec, Z. (Polimery, 2022)
Based on the literature data (144 references mainly from the last 20 years) and own results the review of possible mechanisms of thermal or thermooxidative degradation of polyester thermoplastic elastomers (TPE-E) are reported. A lot of block copolymers differing in the structure of segments are included into this group, among others the commercial copoly(ether-esters) based on PBT, PBN, PEOX or PTMO. The ester group, apart from the other functional groups, can occur as well in the hard and flexible segments. The lifetime of TPE-E is controlled by both oxidation and thermal degradation processes, mostly proceeding independently. Thermal oxidation of ester elastomers may occur during every stage of their life cycles (Fig. 1 - 6): during the synthesis, processing, storage or use of the final goods. The influence of introduction of various additives on the processes of decomposition and ageing of TPE-E (Fig. 7-10) were compared. The proper choice of stabilizers and antioxidants as well as initial substrates let obtain the materials showing excellent useful properties and high resistance to various environmental conditions.